Dried chili seeds separator machine - Husin, Mohd Asri; Shahrudin, Muhammad Shahrunizam; Sapiange, Muhamad Hanif; Abdul Razak, Siti Zarina; Hassan, Mohd Fahrul (Penerbit UTHM, 2017)
Chili is a fruit of Capsicum plants [1]. The fruit is known as vegetable which is cultivated as food. Also, it is known as ‘Lada’ (in East Coast) or chili. It produces small flowers that turn into fruits in every branch of leaves. Chili is rich in vitamin C, vitamin A and minerals such as iron, calcium, phosphorus, sodium and potassium. Moreover, this vegetable is said to be worth in terms of relieving pain associated with obesity. Besides, it is good for blood circulation and to sore throat infections. Additionally, Cayenne pepper contains substance that prevents blood clotting, from a disease called thrombosis [2].